A temperature sensor implant for active implantable medical devices for in vivo subacute heating tests under MRI. Issue 5 (14th September 2017) - Silemek, Berk; Acikel, Volkan; Oto, Cagdas; Alipour, Akbar; Aykut, Zaliha Gamze; Algin, Oktay; Atalar, Ergin
Abstract : Purpose: To introduce a temperature sensor implant (TSI) that mimics an active implantable medical device (AIMD) for animal testing of MRI heating. Computer simulations and phantom experiments poorly represent potential temperature increases. Animal experiments could be a better model, but heating experiments conducted immediately after the surgery suffer from alterations of the thermoregulatory and tissue properties during acute testing conditions. Therefore, the aim of this study was to introduce a temperature sensor implant that mimics an AIMD and capable of measuring the electrode temperature after implantation of the device without any further intervention at any time after the surgery in an animal model. Methods: A battery‐operated TSI, which resembled an AIMD, was used to measure the lead temperature and impedance and the case temperature. The measured values were transmitted to an external computer via a low‐power Bluetooth communication protocol. In addition to validation experiments on the phantom, a sheep experiment was conducted to test the feasibility of the system in subacute conditions. Results: The measurements had a maximum of 0.5°C difference compared to fiber‐optic temperature probes. In vivo animal experiments demonstrated feasibility of the system. Conclusion: An active implant, which can measure its own temperature, was proposed to investigate implant heating during MRI examinations. Magn Reson Med 79:2824–2832, 2018. © 2017 International Society for Magnetic Resonance in Medicine.